Qualitative Review of Academic Advising Perceptions: Some Students Satisfied and Need It, Some Don’t - Sherlywati; Fanny Kristine; Imelda Junita (Humaniora: Journal of Indonesia Culture and Society, 2022)
The research presented experiences in seeking academic advising patterns that produce satisfaction, urgency, and students’ academic and personal development at a university in Bandung, Indonesia. Data were collected using the story circle method. Four questions, including the meaning of advising, memorable experiences, perception of the process and advisors, and student expectations, were asked to answer the two main research questions. The two main questions involved the meaning and benefits of advising and satisfaction. A total of 57 respondents divided into seven groups of story circles were selected as participants using a purposive sampling method. Data were analyzed using a hierarchical Cresswell approach, starting from transcription, coding, categorizing, and developing themes. The results show that some students are satisfied with academic advising, but others feel dissatisfied even though it is important. The results also show that most advisors have created meaningful and memorable stories supporting student academic achievement. However, the relationship between lecturers and undergraduates determines the satisfaction level. The managers suggest from the research that it is necessary to hold coaching and counseling, training for advisors, and set a minimum procedural standard, including equating online communication channels because it minimizes the inequality of students’ satisfaction.